IMPROVING BABY SLEEP QUALITY WITH BABY MASSAGE: Pre-Experimental Research Method - Renince Siregar; Since Desi Inarti; Alvinda Prativi (SABDA EDU PRESS (SEP), 2024)
Sleep is a top priority for babies, so that the body can produce growth hormone and also the brain will grow 3 times from birth. In addition, sleep also provides benefits for the mental, emotional, physical health and immune system of the baby. The journal Pediatrics noted that about 33% of babies experience sleep problems, but they are not detected and not handled properly. Almost 72% of parents do not consider sleep disorders in infants as a problem, even though they can interfere with infant growth, cause impaired immune function, and endocrine system regulation (Sekartini &; Adi, 2016). The purpose of the study was to determine the effect of baby massage on the sleep quality of infants aged 0-6 months at TPMB Rosliana – South Tambun in 2022. Pre-Experimental Research Method with one group pretest-posttest (Adiputra et al., 2021). The results of the study showed the effect of Baby Massage on the quality of sleep of infants aged 0-6 months at TPMB Rosliana With a p value of 0.001 where after massage there was an increase in the quality of baby's sleep, namely before massage harganya 13% of babies with good sleep quality, while after massage 78.3% of babies with good sleep quality.